Membangun Iklim Investasi yang Kondusif: Perlindungan hukum bagi penanam modal dalam sektor perkebunan kelapa sawit di Desa Empus, Kabupaten Langkat - warsiman; Tanjung, Jarnawi Hadi Saputra; Tanjung, Irwansyah; Amalia, Apri; Fauzi, Muhammad (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2025)
The palm oil industry in Indonesia, as one of the country’s major economic sectors, contributes significantly to the national economy. However, this sector faces various challenges, particularly related to legal uncertainty that hinders the creation of a conducive investment climate. This study aims to analyze the legal protection for investors in the palm oil plantation sector, focusing on Empus Village, Langkat Regency. The research explores legal issues related to land ownership, social conflicts with local communities, and policy changes that are poorly coordinated. The method used is a descriptive qualitative approach with triangulation techniques, integrating data from in-depth interviews, field observations, and policy document analysis. The study finds that unclear land ownership and fluctuating policies are the primary obstacles to investment. Additionally, the lack of policy socialization by the government has caused legal uncertainty that disadvantages both investors and local communities. Existing policies, such as Minister of Agriculture Regulation No. 26/2017, do not provide clear and consistent legal protection. Therefore, the study recommends enhancing policy socialization, revising legal protection for investors, and enforcing stronger legal frameworks to create a more conducive and sustainable investment climate. This research contributes to the formulation of more inclusive policies and supports the sustainability of the palm oil plantation sector.